2019
DOI: 10.5424/sjar/2018164-13222
|View full text |Cite
|
Sign up to set email alerts
|

Nile tilapia fingerling cultivated in a low-salinity biofloc system at different stocking densities

Abstract: A 42-day trial was conducted to evaluate the effects of a low-salinity biofloc system with different stocking densities on water quality and zootechnical performance of Nile tilapia fingerlings (10 g/L). Four treatments were tested at different densities: 500 fish/m³, 750 fish/m³, 1,000 fish/m³ and 1,250 fish/m³, all in triplicate. Fingerlings of Oreochromis niloticus (initial mean weight of 1.17 ± 0.05 g) were stocked in twelve experimental black-plastic tanks (40 L) with no water exchange during the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 32 publications
8
27
0
Order By: Relevance
“…Moreover, the low nutritional content of the commercial feed used probably influenced the reduced growth and higher FCR (2.03 to 5.86), due to the low lipid content found in the commercial feed (2.61%), different from the information described in the label. Lima et al (2018) found similar values to those of the present study at a lower time (42 days), from 12.40 to 18.99g, 96.82 to 100% of the survival, and lower values of FCR (1.24-1.40) when cultivating tilapia at different densities in biofloc with 36% protein and 4% lipid feed. However, the difference in the feed conversion factor between treatments with 30% and 50% addition of molasses is due to the fact that the animals of the treatments with the highest application of molasses showed signs of stress.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, the low nutritional content of the commercial feed used probably influenced the reduced growth and higher FCR (2.03 to 5.86), due to the low lipid content found in the commercial feed (2.61%), different from the information described in the label. Lima et al (2018) found similar values to those of the present study at a lower time (42 days), from 12.40 to 18.99g, 96.82 to 100% of the survival, and lower values of FCR (1.24-1.40) when cultivating tilapia at different densities in biofloc with 36% protein and 4% lipid feed. However, the difference in the feed conversion factor between treatments with 30% and 50% addition of molasses is due to the fact that the animals of the treatments with the highest application of molasses showed signs of stress.…”
Section: Discussionsupporting
confidence: 90%
“…A similar result was found by Jung et al (2017) where WC decreased about 82% when supplementation with two microalgae species were used. The WC was similar (52.48 L kg -1 with 500 fish m -3 ) that reported by Lima et al (2018) and lower compared with 750 to 1250 fish m -3 (76.32 to 101.54 L kg -1 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…After the end of this experiment, the three effluents were homogenized and used in the biomass production of the microalga Chlorella vulgaris. The water quality, centesimal composition and the data productivity of Nile tilapia fingerlings in BFT are available in Lima et al (2019).…”
Section: Nile Tilapia Farmingmentioning
confidence: 99%
“…However, there is a discussion about the accumulated nitrogen (N) and phosphorus (P) compoundsduring farming in these systems, which are mainly from feed residues and excreta from cultivated organisms. On average, 75% of the feed-N and 50-70% of feed-P ends up in the water (Crab, Defoirdt, Bossier, & Verstraete, 2012;Lima et al, 2019). This accumulation is due to one of the main characteristics of this system, the stagnant water system (Mishra et al, 2008;Krummenauer, Cavalli, Poersck, & Wasielesky, 2011).…”
Section: Introductionmentioning
confidence: 99%